A identidade do professor de inglês: discursos, narrativas e crenças sobre ensinar inglês no Tocantins - Teixeira, Patrícia Luciano de Farias (2020)
This study presents results of a research carried out with three English language teachers of Tocantins and had as objective to investigate their identities of teacher based on their beliefs and discourses present in their narratives about teaching English. The research is ethnographic, qualitative and interpretative of the data collected through autobiographical narratives and questionnaires, analyzed in the light of theories of Applied Linguistics (RAJAGOPALAN 2003, 2004, 2015, ALMEIDA FILHO 1992, 2001, 2013, 2014, 2015, BARCELOS 2001, 2006a, 2006b) and the French Discourse Analysis (PÊCHEUX, 1983; ORLANDI, 2012a, 2012b, 2015; 2016; CORACINI 2000, 2007; ECKERT-HOFF, 2008). Through the analysis of the discourses present in the autobiographical narratives and the questionnaires it was possible to perceive that these teachers formed and still form their professional identity based on their negative and positive experiences, their experiences in the classroom and beyond, mixed with their perspectives of a Meaningful English teaching for the student. It was also observed that, although teachers understand the teaching of a language as something borderline and sociocultural, they still cannot teach English under these perspectives given the different circumstances imposed by the educational system of the country itself and the region in which it operates. The beliefs that the teachers carry in themselves on the teaching of the English language were being shaped and molded to the soon of their lives as teachers and, from them, transforming their teaching approaches. It is these beliefs, belonging to an identity whole of being a teacher, that are shaping their praxis and by them these teachers are also changing.